Vimentin protects differentiating stem cells from stress - Pattabiraman, Sundararaghavan (2021)
Vimentin is one of the first cytoplasmic intermediate filaments to be expressed in mammalian cells during embryogenesis, but its role in cellular fitness has long been a mystery. Vimentin is acknowledged to play a role in cell stiffness, cell motility, and cytoplasmic organization, yet it is widely considered to be dispensable for cellular function and organismal development. Here, we show that Vimentin plays a role in cellular stress response in differentiating cells, by recruiting aggregates, stress granules, and RNA-binding proteins, directing their elimination and asymmetric partitioning. In the absence of Vimentin, pluripotent embryonic stem cells fail to differentiate properly, with a pronounced deficiency in neuronal differentiation. Our results uncover a novel function for Vimentin, with important implications for development, tissue homeostasis, and in particular, stress response.